The relationship between deficit in digit span and genotype in nonsense mutation Duchenne muscular dystrophy. (25th September 2018) - Thangarajh, Mathula; Elfring, Gary L.; Trifillis, Panayiota; McIntosh, Joseph; Peltz, Stuart W.
Abstract : Objective: To evaluate the relationship between deficit in digit span and genotype in nonsense mutation (nm) Duchenne muscular dystrophy (DMD) (nmDMD). Methods: We investigated the relationship between normalized digit-span forward (d-sf) and digit-span backward (d-sb) scores to the location of nmDMD mutations in 169 participants ≥5 to ⩽20 years who participated in a phase 2b clinical trial. Because alternative promoters are found upstream of DMD exons 30, 45, and 63, we correlated d-sf and d-sb to the specific nmDMD mutation location. Results: Participants with nm downstream of exon 30, downstream of exon 45, and downstream of exon 63 had significantly lower normalized d-sf scores ( p < 0.0001). Participants with nm downstream of exon 45 in addition had significantly lower normalized d-sb score ( p < 0.04). There was no significant difference in the normalized d-sb score in participants with mutations upstream or downstream of DMD exon 30 or upstream or downstream of DMD exon 63. Conclusion: Our data provide evidence that specific cognitive deficits correlate to genotype in individuals with nmDMD, highlighting the critical role of brain-specific dystrophin isoforms in the neurobiological manifestations of this disease. Clinicaltrials.gov identifier: NCT02090959.